2007
DOI: 10.1007/s10338-007-0724-y
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric properties of single-strand DNA molecular brush biolayers

Abstract: The paper is devoted to investigations on nanomechanical behaviors of biochips in label-free biodetections. The chip consists of Si-layer, Ti-layer, Au-layer and single-strand DNA (ssDNA) molecular brush biolayer immobilized by self-assembly technology of thiol group. Unlike previous viewpoints, such as force-bending, entropy-bending and curvature electricity effect, etc., the piezoelectric effect of the biopolymer brush layer is viewed as the main factor that induces nanomechanical bending of biochips, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…Considering nanomechanical deflections and detection precisions (0.1 nm) in the present chip system, an alternative two-variable method (Zhang and Xing 2006;Zhang et al 2007;Zhang and Chen 2008, 2009b, 2010 is used in order to describe the chip deformation more accurately. If the curvature radius at the neutral axis (for zero normal strain) is ρ, the normal strain ε at the location y is…”
Section: Geometrical Relationmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering nanomechanical deflections and detection precisions (0.1 nm) in the present chip system, an alternative two-variable method (Zhang and Xing 2006;Zhang et al 2007;Zhang and Chen 2008, 2009b, 2010 is used in order to describe the chip deformation more accurately. If the curvature radius at the neutral axis (for zero normal strain) is ρ, the normal strain ε at the location y is…”
Section: Geometrical Relationmentioning
confidence: 99%
“…In recent years, microcantilever-based biosensors have attracted much attention (Fritz et al 2000;Wu et al 2001;Hagan et al 2002;Liu et al 2003;Alvarez et al 2004;Hansen and Thundat 2005;Stachowiak et al 2006;Zhang et al 2007;Zhang and Shan 2008;Finot et al 2008;Fritz 2008;Zhang and Chen 2009a;). The low-cost sensors not only exhibit fast response, high sensitivity, and suitability for parallelization into arrays, but also provide common platforms for label-free analyses, such as DNA hybridization, antigen-antibody binding, and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [15] developed a phenomenological model to interpret this phenomenon considering the piezoelectric effect. Curve fitting with the related experimental data showed that the sign of the piezoelectric constant of ssDNA biofilm may control the deflection direction of ssDNA sensors.…”
Section: Introductionmentioning
confidence: 99%